2015
DOI: 10.1039/c5cc06905j
|View full text |Cite
|
Sign up to set email alerts
|

Primary ammonium/tertiary amine-mediated controlled ring opening polymerisation of amino acid N-carboxyanhydrides

Abstract: Stable commercial primary ammonium chlorides were combined with tertiary amines to initiate the controlled ring opening polymerisation of amino acid N-carboxyanhydrides to yield polypeptides with defined end group structure, predetermined molar mass and narrow molar mass distribution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 24 publications
6
34
0
Order By: Relevance
“…FT-IR analyses confirmed the transformation of Poc-Sar into Sar-NCA, by the two characteristic vibration bands (NCA, CvO stretch) at ν = 1775 and 1850 cm −1 (ESI †). 26 As expected, the reaction was dramatically accelerated by the presence of TEA, and quantitative conversion of the Poc-Sar could be achieved within less than 8 hours (≥0.5 equiv. TEA) or 14 hours (0.2 equiv.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…FT-IR analyses confirmed the transformation of Poc-Sar into Sar-NCA, by the two characteristic vibration bands (NCA, CvO stretch) at ν = 1775 and 1850 cm −1 (ESI †). 26 As expected, the reaction was dramatically accelerated by the presence of TEA, and quantitative conversion of the Poc-Sar could be achieved within less than 8 hours (≥0.5 equiv. TEA) or 14 hours (0.2 equiv.…”
supporting
confidence: 72%
“…Ideally, the tertiary amine base does not initiate an uncontrolled polymerization of the Sar-NCA (which is a cyclic tertiary amide without acidic protons), which can only happen with an α-amino acid NCA (deprotonation of the NCA secondary amide and subsequent polymerization via the activated monomer mechanism). 13,26 Also, the released PhO − should be readily protonated (PhOH, pK a 18.0 (DMSO)) 25 by Poc-Sar or by the protonated amine base, leading to a regeneration of the amine base (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, ROP of NCAs can be initiated with either a nucleophile or base . Additionally, organometallic catalysts and a wide range of metal‐free‐initiation approaches as the use of primary amine salts (e.g., primary amine hydrochlorides and primary amine fluoroborates), combined primary/secondary amine systems, combined thiourea/amine systems, N ‐trimethylsilyl amines (e.g., hexamethyldisilazane), or trimethylsilyl sulfides (e.g., phenyl trimethylsilyl sulfide) have been developed. Optimization of the reaction conditions (decreased temperature, removal of carbon dioxide by nitrogen flow or high‐vacuum techniques) further improves the control over the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…Work toward this end has mainly been pioneered by Deming and co-workers [9][10][11] . The ring-opening polymerization (ROP) of α-amino acid N-carboxyanhydrides (NCAs), initiated by amines or amine-derivatives (e.g., amine hydrochlorides 12,13 , amine trifluoroboranes 14 , and silazane derivatives 15,16 ), has emerged as a versatile method due to their advantages, including being a metal-free procedure and the absence of any toxic impurities. Intensive mechanistic studies have shown that two competitive mechanisms (the normal amine mechanism and the activated monomer mechanism) lead to undesirable side reactions, preventing the formation of welldefined polypeptides with controlled molecular weights (MWs) and low polydispersity index (Đ) 17,18 .…”
mentioning
confidence: 99%